Nkrumah and Philosophy of African Unity - Kimaro, Octavian P.; Makokha, Kenneth; Muhenda, John (Advances in Social Sciences Research Journal, 2022)
This article mainly focuses on African unity as understood by Nkrumah. African unity includes the struggle in various fields, political, social and economic. Nkrumah’s ideas about African unity were widely defined as a sustainable political strategy for the well-being of Africans across the continent. Such support fought against corruption and things that hold back the development of the continent. Such ideas also helped to develop African identity and social ideologies. The current leaders of independent African nations should learn from the founders of African nations due to their dreams that focused on the well-being all citizens. In the 21st century there is a need for greater cooperation between all countries within the African continent. What is the most important issue now is to promote African identity. This can be done in the implementation of development goals such as ending problems facing contemporary Africa like civil wars, poverty and individualism.